Depletion of the type 1 IGF receptor delays repair of radiation-induced DNA double strand breaks - Turney, B; Kerr, M; Chitnis, M; Lodhia, K; Wang, Y; Riedemann, J; Rochester, M; Protheroe, A; Brewster, S; Macaulay, V (Elsevier, 2012)
Background and purpose: IGF-1R depletion sensitizes prostate cancer cells to ionizing radiation and DNAdamaging cytotoxic drugs. This study investigated the hypothesis that IGF-1R regulates DNA double strand break (DSB) repair. Methods: We tested effects of IGF-1R siRNA transfection on the repair of radiation-induced DSBs by immunoblotting and immunofluorescence for cH2AX, and pulsed-field gel electrophoresis. Homologous recombination (HR) was quantified by reporter assays, and cell cycle distribution by flow cytometry. Results: We confirmed that IGF-1R depletion sensitized DU145 and PC3 prostate cancer cells to ionizing radiation. DU145 control transfectants resolved radiation-induced DSBs within 24 h, while IGF-1R depleted cells contained 30–40% unrepaired breaks at 24 h. IGF-1R depletion induced significant reduction in DSB repair by HR, although the magnitude of the repair defect suggests additional contributory factors. Radiation-induced G2-M arrest was attenuated by IGF-1R depletion, potentially suppressing cell cycle-dependent processes required for HR. In contrast, IGF-1R depletion induced only minor radiosensitization in LNCaP cells, and did not influence repair. Cell cycle profiles were similar to DU145, so were unlikely to account for differences in repair responses. Conclusions: These data indicate a role for IGF-1R in DSB repair, at least in part via HR, and support use of IGF-1R inhibitors with DNA damaging cancer treatments.